Chorus source region localization in the Earth's outer magnetosphere using THEMIS measurements - O. Agapitov; O. Agapitov; V. Krasnoselskikh; Yu. Zaliznyak; Yu. Zaliznyak; V. Angelopoulos; O. Le Contel; G. Rolland (Annales Geophysicae, 2010)
Discrete ELF/VLF chorus emissions, the most intense electromagnetic plasma waves observed in the Earth's radiation belts and outer magnetosphere, are thought to propagate roughly along magnetic field lines from a localized source region near the magnetic equator towards the magnetic poles. THEMIS project Electric Field Instrument (EFI) and Search Coil Magnetometer (SCM) measurements were used to determine the spatial scale of the chorus source localization region on the day side of the Earth's outer magnetosphere. We present simultaneous observations of the same chorus elements registered onboard several THEMIS spacecraft in 2007 when all the spacecraft were in the same orbit. Discrete chorus elements were observed at 0.15–0.25 of the local electron gyrofrequency, which is typical for the outer magnetosphere. We evaluated the Poynting flux and wave vector distribution and obtained chorus wave packet quasi-parallel propagation to the local magnetic field. Amplitude and phase correlation data analysis allowed us to estimate the characteristic spatial correlation scale transverse to the local magnetic field to be in the 2800–3200 km range.